2020
DOI: 10.3904/kjim.2017.233
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Friedewald formula for estimating low density lipoprotein cholesterol: the Korea National Health and Nutrition Examination Survey, 2009 to 2011

Abstract: The Friedewald equation tends to underestimate LDL-C in highrisk subjects such as hypertriglyceridemia and hypo-HDL-cholesterolemia. For these individuals accurate assessment of LDL-C is crucial, and therefore additional evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
0
15
1
Order By: Relevance
“…Repeated measurement would have been more accurate for classifying the participants. Second, several studies [38, 39] have shown that even when the TG level is < 400 mg/dL, a higher TG level can increase the degree to which the Friedewald formula underestimates LDL-C level. We excluded participants with a TG level > 400 mg/dL, but we also analyzed non-HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated measurement would have been more accurate for classifying the participants. Second, several studies [38, 39] have shown that even when the TG level is < 400 mg/dL, a higher TG level can increase the degree to which the Friedewald formula underestimates LDL-C level. We excluded participants with a TG level > 400 mg/dL, but we also analyzed non-HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of cholesterol were measured enzymatically. If the TG level was <400 mg/dL, the LDL-C level was calculated using the Friedewald Equation [ 14 ]. The LDL-C level was measured with direct assay when the TG level was >400 mg/dL.…”
Section: Methodsmentioning
confidence: 99%
“…An autoanalyzer (Hitachi Ltd., Tokyo, Japan) was used to determine serum concentrations of glucose, HDL, TG, aspartate transaminase (AST), and alanine transaminase (ALT). The Friedwald equation was used to calculate low-density lipoprotein cholesterol (LDL) as follows: LDL = total cholesterol—HDL—(TG/5), when TG was <400 mg/dL [ 2 , 17 ]. When TG was above 400 mg/dL, TG was measured directly on the Hitachi 7600 auto-analyzer.…”
Section: Methodsmentioning
confidence: 99%